2019
DOI: 10.3389/fmicb.2019.02600
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Antimicrobial Resistance Traits of Vibrio cholerae Non-O1/Non-O139 Isolated From a Large Austrian Lake Frequently Associated With Cases of Human Infection

Abstract: Vibrio cholerae belonging to serogroups other than O1 and O139 are opportunistic pathogens which cause infections with a variety of clinical symptoms. Due to the increasing number of V. cholerae non-O1/non-O139 infections in association with recreational waters in the past two decades, they have received increasing attention in recent literature and by public health authorities. Since the treatment of choice is the administration of antibiotics, we investigated the distribution of antimicrobial resistance prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
(89 reference statements)
1
22
0
Order By: Relevance
“…19 Resistant V. cholerae isolates that originated from clinical and environmental sources have been reported. 18,[20][21][22][23][24] For example, during an outbreak of cholera in Guinea-Bissau in 1996-1997, casefatality rates increased from 1% to 5.3% after the emergence of multidrug-resistant (MDR) V. cholerae. 20 Chomvarin et al reported that V. cholerae O1 strains (n = 35) isolated from clinical samples and natural surface water sources in Thailand were resistant to trimethoprim (TM)/sulfamethoxazole and/or tetracycline (TET)/or ampicillin (AMP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Resistant V. cholerae isolates that originated from clinical and environmental sources have been reported. 18,[20][21][22][23][24] For example, during an outbreak of cholera in Guinea-Bissau in 1996-1997, casefatality rates increased from 1% to 5.3% after the emergence of multidrug-resistant (MDR) V. cholerae. 20 Chomvarin et al reported that V. cholerae O1 strains (n = 35) isolated from clinical samples and natural surface water sources in Thailand were resistant to trimethoprim (TM)/sulfamethoxazole and/or tetracycline (TET)/or ampicillin (AMP).…”
Section: Introductionmentioning
confidence: 99%
“…24 Lepuschitz et al investigated V. cholerae isolates (n = 82) recovered from an Austrian lake, and they found that the majority of the isolates showed resistance to sulfonamides (n = 80), and some to streptomycin (STR; n = 32) and AMP (n = 17). 23 Xu et al reported that *65.3% of V. cholerae isolates (n = 400) from four species of commonly consumed fish in Shanghai, China were resistant to STR, followed by AMP (44.5%) and rifampicin (RIF; 24.0%). 18 Heavy metals used in mining, fossil fuel combustion, and agricultural practices can enter the food chain, such as cadmium (Cd), chromium (Cr), mercury (Hg), and Pb.…”
Section: Introductionmentioning
confidence: 99%
“…The inappropriate use of antibiotics has resulted in considerably increased toxicogenic V. cholerae and difficulties in clinical case treatment [ 39 , 40 ]. The aquatic environment is a reservoir of V. cholerae and might be an important source of resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical strains may also contaminate environmental strains (25). The discovery of MDR environmental isolates of VC without MGEs are also of major concern (210,211). Chromosomal inheritance of genes acquired by HGT and integrated with the chromosome are vertically transferred leading to inherited AMR traits and highlights the eventual disastrous consequences of HGT lying in chromosomal inheritance of laterally acquired traits (212).…”
Section: Discussionmentioning
confidence: 99%
“…These integrate with the chromosome and are vertically inherited by later generations (212). Therefore, acquisition of AMR by HGT (210,211) leads to persistence of AMR against common antibiotics in future generations (212). Tables 3-5 enumerate the different resistance markers associated with VC antibiotic resistance (AR) and which are useful for rapid screening and molecular detection of AMR.…”
Section: Discussionmentioning
confidence: 99%